การพัฒนาผลิตภัณฑ์ข้าวพองจากข้าวเหนียวเขี้ยวงูอินทรีย์ - ช่วยพัฒน์ วรรณศิกา; อธินุวัฒน์ ดุสิต; ด่านขับต้อน ดวงกมล; ผลประไพ ชนัญ (Thai Journal of Science and Technology, 2020)
The purpose of this research was to develop of puffed rice product from organic Kiaw Ngoo sticky rice with modified syrup to product forming. The suitable manufacturing process in this production was also studied. We found that soaking glutinous rice in butterfly pea flower juice showed highest significantly (p ≤ 0.05) of a* value and texture value of puffed rice with 6.04±0.18 and 21.93±0.39 N, respectively when compared with those of other treatments. Subsequently, three treatments of puffed rice product forming modified syrup were investigated. We found that the formula 2; 10 g of glucose syrup and water and 5 g of stevia, gave the highest customer acceptances of the product including the best aroma, texture value, taste, and overall liking of puffed rice product with 6.7±0.20, 7.3±0.04, 7.2±0.03, and 7.4±0.04, respectively. Moreover, the formula 2 showed the best texture value and moisture content of the product with 20.56±0.18 N and 1.5±0.10 %, respectively. This indicated that the best process for puffed rice product was soaking glutinous rice in butterfly pea flower juice for 10-12 h, steamed with boiled water for 25 min, dried with solar energy for 24 h, and fried in boiled oil at 190 ºC. Then, 100 g of puffed rice were formed with modified syrup including 10 g of glucose syrup and water and 5 g of stevia.